2016
DOI: 10.1007/s12035-016-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Ameliorates Rotenone-Induced Parkinson’s Disease in Rats: Involvement of Its Anti-Inflammatory and Anti-Apoptotic Actions

Abstract: Parkinson's disease (PD) is a slowly progressive neurodegenerative movement disorder. Apoptosis, neuroinflammation, and oxidative stress are the current hypothesized mechanisms for PD pathogenesis. Tetramethylpyrazine (TMP), the major bioactive component of Ligusticum wallichii Franchat (ChuanXiong), Family Apiaceae, reportedly has anti-apoptotic, anti-inflammatory and antioxidant effects. This study investigated the role of 'TMP' in preventing rotenone-induced neurobiological and behavioral sequelae. A prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 87 publications
2
29
0
Order By: Relevance
“…Accumulation of α-synuclein in Lewy bodies is an key pathological event in PD and enhanced expression of α-synuclein influences neuronal death by either necrosis or apoptosis [ 42 ]. Moreover, impairment of autophagy results in accumulation of aggregated α-synuclein protein favoring neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of α-synuclein in Lewy bodies is an key pathological event in PD and enhanced expression of α-synuclein influences neuronal death by either necrosis or apoptosis [ 42 ]. Moreover, impairment of autophagy results in accumulation of aggregated α-synuclein protein favoring neurodegeneration.…”
Section: Resultsmentioning
confidence: 99%
“…PD is the second most common neurodegenerative disease and is characterized by a loss of dopaminergic neurons . Some environmental risk factors, such as ROT and MPP + , are used as neurotoxins for evaluating potential neuroprotective strategies against apoptotic diseases like PD . For in vitro PD studies, the SH‐SY5Y human neuroblastoma cell line is frequently used as a cell model, because it exhibits many characteristics of dopaminergic neurons .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Some environmental risk factors, such as ROT and MPP + , are used as neurotoxins for evaluating potential neuroprotective strategies against apoptotic diseases like PD. [26][27][28][29][30] For in vitro PD studies, the SH-SY5Y human neuroblastoma cell line is frequently used as a cell model, because it exhibits many characteristics of dopaminergic neurons. 31,32 In the present study, we demonstrated that both RBM3 and mild hypothermia protect SH-SY5Y cells from ROT-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of theory of TCM, kidney deficiency is the basis of amnesia and other cognitive deficits, while phlegm and blood stasis are significant pathological factors. For this reason, amounts of experiments and trials have been carried out and shown specific effects against cognitive decline, which involve Alpiniae oxyphyllae fructus [27], Ligusticum wallichii [28][29][30], curcuma [31][32], Fructus gardenia [33][34], Radix notoginseng [35][36]. Meanwhile, an herbal formula named Yi-Zhi-An-Shen (YZAS) Granules has been composed of Lophatherum gracile and medical herbs mentioned above, which is designed for aiding the treatment of cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%